Pengaruh Komunikasi Interpersonal Dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat Di Kelurahan Palmeriam Jakarta Timur - Rina Karlina; Sukarni Novita Sari; Juardi (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This study aims to analyze the influence of interpersonal communication and service quality on public satisfaction at Palmeriam Urban Village, East Jakarta. The study employed a quantitative approach with a causal associative method. The sample consisted of 99 respondents selected through accidental sampling. The results indicate that interpersonal communication has a positive and significant effect on public satisfaction with a contribution of 10.1%. Service quality also has a positive and significant effect with a contribution of 8.2%. Simultaneously, interpersonal communication and service quality significantly influence public satisfaction with a contribution of 14.7%. Keywords: Interpersonal Communication, Service Quality, Public Satisfaction, Public Service